Formation of Elemental Selenium Nanoparticles (SeNPs) from the Reduction of Selenite (SeO32-) by a Pure Culture of Pseudomonas Stutzeri NT-i, - Job T. Tendenedzai (Chemical Engineering Transactions, 2021)
Selenite (SeO32-), the most toxic and most reactive selenium (Se) oxyanion can be reduced to elemental selenium (Se0) by a variety of bacteria, including Pseudomonas stutzeri NT-I. Se0 is in the form of selenium nanoparticles (SeNPs), which are relatively less toxic. The development of SeNPs has gained commercial interest as they have various applications. Examples include uses in the photoelectrical and medicinal fields. In this study, Pseudomonas stutzeri NT-I, a bacterium exhibiting high selenite tolerance and reduction capacity, was used in aerobic batch reduction experiments (36 h, 120 rpm, 35±2 °C, pH =7). Thereafter, the SeNPs were harvested, recovered and analysed. Transmission Electron Microscopy (TEM) analysis indicated the biogenesis of extracellular spherical electron-dense SeNPs, as confirmed by abiotic control. Other key results indicated that more Se0 was recovered when reducing higher SeO32- concentrations. This implies that more SeO32- had been reduced for the 10 mM SeO32- concentration compared to the 0.5 and 2 mM SeO32- concentrations, even though there was constant biomass (5 g.L-1) in all experiments. Findings from this study confirm that strain NT-I can reduce SeO32- to Se0 which can be recovered for other applications. Moreover, it sheds more light on the mechanism of reduction employed by the bacteria as it appears to occur extracellularly as per the TEM images.